THE FUTURE OF DESIGN: 3D MODELING AND ITS IMPACT - Suyunova Ugilshod Anvar qizi; Qurbonov Xurshid Narzulla o’g’li (Journals Park Publishing, 2023)
The article explores the future of design and how 3D modeling technology is transforming the way designers and manufacturers create products. The article discusses the impact of 3D modeling technology on various industries, including architecture, automotive, and fashion. The article concludes by discussing the potential impact of 3D modeling technology on the future of design, including increased customization and personalization of products, streamlined manufacturing processes, and reduced waste and environmental impact. The article emphasizes the importance of staying up-to-date with the latest advancements in 3D modeling technology to stay competitive in the design industry.